Optimal. Leaf size=23 \[ e^{\frac {1}{2} \left (-\frac {e^{-2 x}}{x}+\log ^2(4)\right )}+x \]
________________________________________________________________________________________
Rubi [F] time = 1.05, antiderivative size = 0, normalized size of antiderivative = 0.00, number of steps used = 0, number of rules used = 0, integrand size = 0, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.000, Rules used = {} \begin {gather*} \int \frac {e^{-2 x} \left (2 e^{2 x} x^2+e^{\frac {e^{-2 x} \left (-1+e^{2 x} x \log ^2(4)\right )}{2 x}} (1+2 x)\right )}{2 x^2} \, dx \end {gather*}
Verification is not applicable to the result.
[In]
[Out]
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\frac {1}{2} \int \frac {e^{-2 x} \left (2 e^{2 x} x^2+e^{\frac {e^{-2 x} \left (-1+e^{2 x} x \log ^2(4)\right )}{2 x}} (1+2 x)\right )}{x^2} \, dx\\ &=\frac {1}{2} \int \left (2+\frac {e^{\frac {1}{2} \left (-\frac {e^{-2 x}}{x}-4 x+\log ^2(4)\right )} (1+2 x)}{x^2}\right ) \, dx\\ &=x+\frac {1}{2} \int \frac {e^{\frac {1}{2} \left (-\frac {e^{-2 x}}{x}-4 x+\log ^2(4)\right )} (1+2 x)}{x^2} \, dx\\ &=x+\frac {1}{2} \int \left (\frac {e^{\frac {1}{2} \left (-\frac {e^{-2 x}}{x}-4 x+\log ^2(4)\right )}}{x^2}+\frac {2 e^{\frac {1}{2} \left (-\frac {e^{-2 x}}{x}-4 x+\log ^2(4)\right )}}{x}\right ) \, dx\\ &=x+\frac {1}{2} \int \frac {e^{\frac {1}{2} \left (-\frac {e^{-2 x}}{x}-4 x+\log ^2(4)\right )}}{x^2} \, dx+\int \frac {e^{\frac {1}{2} \left (-\frac {e^{-2 x}}{x}-4 x+\log ^2(4)\right )}}{x} \, dx\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.26, size = 25, normalized size = 1.09 \begin {gather*} e^{-\frac {e^{-2 x}}{2 x}+\frac {\log ^2(4)}{2}}+x \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.61, size = 25, normalized size = 1.09 \begin {gather*} x + e^{\left (\frac {{\left (4 \, x e^{\left (2 \, x\right )} \log \relax (2)^{2} - 1\right )} e^{\left (-2 \, x\right )}}{2 \, x}\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [A] time = 0.14, size = 37, normalized size = 1.61 \begin {gather*} {\left (x e^{\left (-2 \, x\right )} + e^{\left (\frac {4 \, x \log \relax (2)^{2} - 4 \, x^{2} - e^{\left (-2 \, x\right )}}{2 \, x}\right )}\right )} e^{\left (2 \, x\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.07, size = 23, normalized size = 1.00
method | result | size |
risch | \(x +{\mathrm e}^{\frac {4 x \ln \relax (2)^{2}-{\mathrm e}^{-2 x}}{2 x}}\) | \(23\) |
norman | \(\frac {\left ({\mathrm e}^{2 x} x^{2}+x \,{\mathrm e}^{2 x} {\mathrm e}^{\frac {\left (4 x \ln \relax (2)^{2} {\mathrm e}^{2 x}-1\right ) {\mathrm e}^{-2 x}}{2 x}}\right ) {\mathrm e}^{-2 x}}{x}\) | \(51\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.68, size = 19, normalized size = 0.83 \begin {gather*} x + e^{\left (2 \, \log \relax (2)^{2} - \frac {e^{\left (-2 \, x\right )}}{2 \, x}\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 2.67, size = 19, normalized size = 0.83 \begin {gather*} x+{\mathrm {e}}^{2\,{\ln \relax (2)}^2-\frac {{\mathrm {e}}^{-2\,x}}{2\,x}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.19, size = 26, normalized size = 1.13 \begin {gather*} x + e^{\frac {\left (2 x e^{2 x} \log {\relax (2 )}^{2} - \frac {1}{2}\right ) e^{- 2 x}}{x}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________